STRATEGI PERENCANAAN PENGEMBANGAN DESA WISATA TERASERING SITTENGGONG DI DUSUN NAMPAN DESA SUKOMAKMUR KECAMATAN KAJORAN KABUPATEN MAGELANG - Tsafira Azmira, Risa; Nurcahyanto, Herbasuki (Journal of Public Policy and Management Review, 2025)
This research is a qualitative study which aims to recommend planning strategies for the development of the Sitenggong Terraced Tourism Village. This research uses the strategic planning theory proposed by John. M Bryson. This research uses an exploratory qualitative method with SWOT analysis techniques and Litmus test calculations to formulate strategies. The results of this research show that the strategy owned by the Sitenggong Terraced Tourism Village still has many shortcomings so it needs to be improved. The results of the SWOT analysis found 11 strategic development issues, which after carrying out a litmus test obtained 3 issues with strategic characteristics that could be applied in development. Researchers recommend the following strategy, namely increasing cooperation with the community, especially in terms of finance or development investment in order to utilize the potential of Mount Sumbing and Vegetable Terraces more optimally. Improving public sector coordination, namely the Magelang Regency Disparpora, in various training and assistance to advance the Sitenggong Terrace Tourism Village, which is still relatively new. Increasing the use of technology through social media, namely Instagram, YouTube and TikTok as promotional media to provide information regarding photo spots that are attractive to tourists.